2018
DOI: 10.3390/su10103804
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climate Change on Spring Maize (Zea mays L.) Suitability across China

Abstract: Spring maize (Zea mays L.) is a thermophilic C4 crop which is sensitive to climate change. This paper provides a detailed assessment of the effect of climate change on the crop from a new perspective, by predicting the probability of the potential distribution of spring maize across China. The affected area of spring maize suitability was identified, and then the affected area was subdivided into the improved area and the deteriorated area. Our results confirmed that there was a detrimental consequence for spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Our studies used high-stability of meteorological yield to improve the traditional methods for the more statistically significant climate indicators, and it is more meaningful to capture the impact of climate change on crops in specific regions. Comparing the research results for maize suitability, based on the MaxEnt model in China [49], it is found that the climate suitability in Jilin Province is basically consistent with our study. However, combined with the actual maize yield data (Figure 3h), the result of Ye et al, is relatively high in the western region, and our study is closer to the actual maize production in Jilin Province.…”
Section: Improvement Of the Climate Suitability Assessment Approachsupporting
confidence: 87%
“…Our studies used high-stability of meteorological yield to improve the traditional methods for the more statistically significant climate indicators, and it is more meaningful to capture the impact of climate change on crops in specific regions. Comparing the research results for maize suitability, based on the MaxEnt model in China [49], it is found that the climate suitability in Jilin Province is basically consistent with our study. However, combined with the actual maize yield data (Figure 3h), the result of Ye et al, is relatively high in the western region, and our study is closer to the actual maize production in Jilin Province.…”
Section: Improvement Of the Climate Suitability Assessment Approachsupporting
confidence: 87%
“…This is in agreement with the findings of related studies that found the model is applicable in assessing crop suitability. Examples are studies on rice by Duan and Zhou [20] and Liu et al [21]; maize by Machovina and Feeley [57], Ji et al [58] and He and Zhou [18]; and banana by Machovina and Feeley [57]. This then confirms MaxENT's capacity, which is based on machine learning and the principle of maximum entropy in estimating the multivariate distribution of habitat suitability conditions for crop suitability.…”
Section: Discussionmentioning
confidence: 55%
“…Plant secondary metabolites synthesis and accumulation were influenced by climate factors including precipitation, temperature, wind speed and annual sunshine duration ( Ji et al, 2018 , Wang et al, 2021 , Wang et al, 2021 ). Appropriate precipitation had an important regulatory effect on the growth and development of plants, the accumulation of components in fruit and the formation of fruit quality.…”
Section: Discussionmentioning
confidence: 99%